A Revisit of Internal Force Diagrams on Nanobeams with Surface Effects - Zhao, De M.; Liu, Jian Lin; Sun, Jing; Wu, Run Ni; Xia, Re (Current Nanoscience, 2015)
It is evident that surface effects dealing with decreasing characteristic size play an extremely important role in the mechanical behaviors of nanoscale structures, from the one-dimensional nanowire to complex micro/nano device. In the present study, the impact of surface effects on the internal forces of a nanobeam is evaluated in terms of the action of the residual surface stress and surface elasticity. Through deriving the expressions of the shear force and bending moment analytically, we depicted the updated internal force diagrams accordingly. Unlike the classical ones in mechanics of materials, the nanobeams take on a strong size-dependent feature. These analyses hold great potential for modulating the mechanical performance of micro/nano materials, and the obtained results provide new insight into the education innovation on mechanics of materials.
Keywords: surface effects